Learning from Practice: How East Lancashire Hospitals' Pharmacy Service Has Embraced Information Technology - Alistair Gray; Clare Mackie; William Price; Emma Coupe; Susan Holgate; Emma Watson; John Eatough; Neil Fletcher; Karen Hodson; Efi Mantzourani (MDPI AG, 2020)
The ethos of the pharmacy service at East Lancashire Hospitals NHS Trust (ELHT) could be described as 'let's make things better'. We have a history of innovation involving technology and people; one without the other does not work but together they are synergistic. The Trust currently does not have an electronic patient record (ePR) or electronic prescribing and medicines administration (ePMA), although we do have electronic prescribing for chemotherapy. However, like all Trusts, we have many electronic systems which offer interoperability, or can support making it easier for the pharmacy team to do a good job. This article describes the many fronts we have worked on over the last ten plus years. Taken individually, the elements cannot be considered as revolutionary; together, they have helped us develop and deliver the safe, personal and effective pharmacy service that we call dedicated ward pharmacy.